1991
DOI: 10.1136/jcp.44.11.958
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma arising in endometriosis of the ovary.

Abstract: Squamous cell carcinoma arising in ovarian endometriosis is extremely rare, but a case is reported in a 62 year old woman. If such an ovarian tumour is discovered evidence of teratoma, Brenner tumour, or endometriosis should be sought. Extensive sampling is mandatory as the developing tumour often overgrows the foci of endometriosis, thus obliterating evidence of its origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
(1 reference statement)
0
13
0
1
Order By: Relevance
“…Young et al 10 have identified epidermoid cysts, some in concert with small Walthard rests, but in the absence of any other teratomatous features. Other case reports and small series [11][12][13][14][15][16][17][18][19] have identified de novo squamous cell carcinoma of the ovary, some associated with endometriosis. By all accounts, these entities are exceedingly rare, and questions remain about their histogenesis.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Young et al 10 have identified epidermoid cysts, some in concert with small Walthard rests, but in the absence of any other teratomatous features. Other case reports and small series [11][12][13][14][15][16][17][18][19] have identified de novo squamous cell carcinoma of the ovary, some associated with endometriosis. By all accounts, these entities are exceedingly rare, and questions remain about their histogenesis.…”
Section: Epidemiologymentioning
confidence: 99%
“…The radiologic findings generally show a solid and cystic mass, usually about 10 to 15 cm in maximal dimension. [6][7][8][9][10][11][12][13][14][15][16][17][18] This latter fact may be helpful in sorting out the preliminary differential diagnosis, given that many aggressive ovarian neoplasms are much larger. Areas of necrosis are often visible, and there are often adhesions to surrounding pelvic structures.…”
Section: Clinical Presentation and Workupmentioning
confidence: 99%
See 3 more Smart Citations